A fractional-step thermal lattice Boltzmann model for high Peclet number flow. (September 2015) - Deng, Lin; Zhang, Yun; Wen, Yanwei; Shan, Bin; Zhou, Huamin
Abstract: As a promising approach in hydrodynamics and thermodynamics modeling, the lattice Boltzmann method (LBM) still suffers severe numerical instability when the temperature field of the flow is convection-dominant (high Peclet number). Despite a lot of research devoted to solve this problem worldwide, to simulate high Peclet number thermal flow at comparably few computational cost is still a hard work, making it inefficient in practical use. In this paper, we combine the LBM and the fractional-step method to propose a novel and stable thermal lattice Boltzmann scheme for high Peclet number flow without refining the lattice. By numerical tests of thermal Poiseuille flow and Couette flow, we quantify second-order accuracy of the proposed model, and through several cases of Peclet number from low to high, the superior stability and efficiency compared with existing thermal lattice Boltzmann model.